How do urban dwellers identify with features within urban green spaces in the Eastern Cape? - Manyani, Amanda (Rhodes University, Faculty of Science, Department of Environmental Science, 2019)
Public urban green spaces contain natural and artificial features which play crucial roles in supporting urban social-ecological systems, a fact now recognized globally. The various natural and artificial features contained in public urban green spaces are said to be key contributors to the quality of life and well-being of urban dwellers. Nevertheless, this has been largely ignored in urban design in South Africa, especially in the poorer township and Reconstruction Development Program (RDP) areas. At the individual household and community levels within the poorer communities, the provision of green spaces and trees, as well as recreation facilities, is well below world standards, and much less than what is available in the more affluent areas of South African towns. Additionally, most research on the links between nature and human well-being in urban contexts comes from developed world contexts which adopt a westernized view of the relationship. Yet, in many societies of the Global South, including South Africa, worldviews and experiences of nature in green spaces and use of other recreational features takes on different meanings to those of the Global North. To show these differences, a combination of methods was used in this study, different types of green spaces were assessed and evaluated by structured observations so as to record the features present within the spaces. A survey of 360 households was conducted by targeting green space users and households within 100 metres from a green space. Results indicated that, across all the green space types, formal green spaces had a low cover of shrubs, trees and herbs whilst having high lawn cover. Furthermore, vegetation had poor rating across all the green spaces since the vegetation was either overgrown herbs, dense thickets of shrubs and mostly alien trees that were either diseased or forked. Similar to the disparity in the composition and structure of vegetation within the green spaces, there was a wide variability in the composition of recreational features and amenities across the green spaces. The formal green spaces had the most amenities like play equipment, shelter and seating. Informal green spaces and commonages had little or no recreational features available. The attributes of these spaces therefore influenced the reasons for visiting as more than 90 % of the respondents simply used the spaces for transit. With regards to attitudes and preferences towards particular features, they were emerging sense of strong negative feelings towards natural features. Most respondents emphasized the need for green spaces that are well laid out with maintained lawns, recreational facilities and open vegetation. Thus, the current design and available features within the studied urban green spaces do not meet local needs and aspirations and thus do not contribute to better well-being and quality of life as much as they could. Specifically, the various health benefits linked with being in contact with nature in the public green spaces were not evident in this study. The South African specific context in green space use, perception and people's preferences is thus crucial for urban planning and sustainability.
Keywords: Land use, Urban -- South Africa; Greenbelts -- South Africa; City planning -- South Africa